Manajemen Pendidikan: Konsep, Hakikat, dan Fungsi dalam Pendidikan - Sulkifli; Yuniarty Mukhtar; Nurfatimah Khumairah; Ummu Rodhatul Muthmainnah Ema Bona; Zulfika Amalia Amalia (Culture education and technology research (Cetera), 2025)
Educational management is a process of managing all components of education systematically to achieve effective and efficient educational goals. This study discusses the definition of educational management as a basis for understanding the importance of structured management in the educational environment. The benefits of educational management include improving the quality of learning, optimizing resources, and achieving institutional goals in a targeted manner. Principles such as efficiency, effectiveness, accountability, and participation serve as guidelines in its implementation. The scope of educational management includes management of students, educators, curriculum, facilities and infrastructure, finance, and public relations. In addition, the nature of the function of educational management consists of planning, organizing, implementing, supervising, and highly competitive education system.